Konsep Kampanye Edukasi “Berseri” sebagai Media Edukasi Orang Tua tentang Sensory Play pada Balita - Fauziah, Lailatul Jannah; Chidtian, Aileena Solicitor Costa Rica El; Nisa, Diana Aqidatun (VISA: Journal of Vision and Ideas, 2025)
Sensory stimulation is a fundamental aspect in supporting the growth and development of children, particularly during the golden age or early childhood (0–5 years). Sensory play serves as an effective method as it integrates playful elements with stimulation of the seven fundamental sensory systems in toddlers. However, many parents from lower-middle socioeconomic backgrounds still lack awareness of the importance of sensory stimulation in establishing a strong foundation for child development. This study aims to design and implement an educational campaign titled Berseri as a form of social intervention to raise parental awareness regarding the significance of sensory stimulation. The research method for designing this educational campaign follows a mixed-methods approach with descriptive analysis. Data were collected through questionnaires, participatory observation, and interviews. The campaign was conducted in three sub-districts of Surabaya—Wonokromo, Tambaksari, and Semampir—selected based on preliminary findings indicating low levels of parenting literacy among the local population. The methods involved a social campaign approach utilizing educational media, distribution of sensory play kits, and collaboration with community health posts (posyandu) and healthcare workers. The results indicate that the implementation of the Berseri campaign had a positive impact on increasing parents’ knowledge and awareness of the importance of sensory stimulation. Furthermore, the campaign successfully facilitated constructive dialogue between program implementers and the community, and encouraged behavioral change in parenting practices. These findings suggest that educational campaigns can serve as an effective strategy for conveying essential information related to child development. The sustainability of such programs is expected to contribute to the improvement of parenting quality and holistic early childhood education.